ANALISIS PRESIDENTIAL THRESHOLD PERSPEKTIF UNDANG-UNDANG NOMOR 7 TAHUN 2017 DAN FIQH SIYASAH - Widiastuti, Nining; Rohmah, Siti Ngainnur; Rahim, Abdur (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
General elections are indeed considered as a symbol as well as the main and first benchmark of democracy, the purpose of general elections is to carry out people’s sovereignty and exercise citizens’ human rights. The Presidential Threshold or parliamentary threshold has the potential to harm the rights of a Candidate Pair to be proposed by a Political Party or a Joint Election Contesting Political Party. If viewed from the perspective of Islamic law, the requirements for a head of state and the electoral system can be studied in the realm of Fiqh Siyasah Dusturiyah, namely the appointment of an imam (caliph). The purpose of this study is to find out the results of the Presidential Threshold Analysis from the Perspective of Law Number 7 of 2017 and Fiqh Siyasah. The method used in this research is the normative legal research method, also known as doctrinal legal research or library research. The results of this study are: (1) Analysis of the Presidential Threshold Perspective of Law Number 7 of 2017, the Presidential Threshold changes to 20% of the number of seats in the DPR or 25% of valid votes nationally in the previous DPR member elections. The policy of continuing to apply the Presidential Threshold is to strengthen the presidential system, because it will force political parties to consolidate politics so that a coalition of political parties supporting the president appears, (2) Analysis of the Presidential Threshold from the Fiqh Siyasah Perspective, the concept of the Presidential Threshold in Law Number 7 of 2017 concerning Elections In general, it is not yet known in the study of Siyasah Fiqh, especially in the process of succession of state leaders. Instead, there is a leadership election mechanism in two ways, namely the election or appointment is carried out by the ahlu al-hal wa al-’aqdi formation council and the appointment is carried out by nomination by the previous caliph.